Anticholinesterase and antioxidant effects of the ethanol extract, ethanol fractions and isolated flavonoids from Cistus laurifolius L. leaves - Akkol, Esra Kupeli; Orhan, Ilkay Erdogan; Yesilada, Erdem (Elsevier Sci Ltd, 2012)
In the current study, the n-hexane, chloroform, ethyl acetate, water, and n-butanol fractions obtained from the main ethanol extract of Cistus launfolius L were evaluated for their cholinesterase inhibitory effects against acetyl- (AChE) and butyrylcholinesterase (BChE), at 50, 100, and 200 mu g/ml, using an ELISA microplate reader. The antioxidative effect of the extract and fractions was also determined using 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity, ferrous ion-chelation capacity, and ferric-reducing antioxidant power (FRAP) test systems. Total phenol and flavonoid contents of the extract and fractions were calculated using Folin-Ciocalteau and aluminium chloride reagents. Three flavonoid derivatives; 3-O-methylquercetin (1), 3,7-O-dimethylquercetin (2), and 3,7-O-dimethylkaempferol (3) isolated from the CHCl(3) fraction were also tested in the same manner. Our experimental findings indicated that the ethanol extract exerted the highest AChE inhibition (80.07 +/- 1.06% at 200 mu g/ml). The ethyl acetate and n-butanol fractions displayed the best activity against DPPH and FRAP assays. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Cistus laurifolius; Cholinesterase inhibition; Antioxidant; Ethanol extract; Flavonoid